Pengembangan Sistem Pemantauan Kesehatan dan Keselamatan Kerja Berbasis IoT di Kawasan Industri Pulogadung - Mayori, Ersha; Sungkono, Sungkono; Widana, I Dewa Ketut Kerta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Occupational health and safety (OHS) is a crucial aspect in maintaining worker productivity and well-being in industrial areas. This study aims to develop an Internet of Things (IoT)-based OHS monitoring system in the Pulogadung Industrial Area, Jakarta. The system is designed to monitor workplace environmental conditions in real-time, including temperature, humidity, hazardous gases, and workers’ heart rates, using sensors connected to a digital platform. The collected data are transmitted to a central server and displayed through a web-based dashboard, allowing management to perform rapid and accurate monitoring and decision-making. The research method includes user needs analysis, system design, prototype implementation, and performance testing. The test results show that the system can provide early warnings of potential hazards and enhance workers’ awareness of OHS conditions. By integrating IoT technology, this system has the potential to strengthen risk management and support the creation of a safer and healthier working environment in industrial areas.